Optimal scheme of open design based on co-designer involvement and the dynamic FBSC model. (4th March 2023) - Li, Shipei; Tang, Dunbing; Wang, Qi; Zhu, Haihua; Niu, Ruixia
Abstract : With the development of Internet technologies, consumers can become involved in the process of product design to share requirements and technical knowledge, which are considered as the utilisable design resources. Function-behaviour-structure (FBS) modelling as a means of knowledge acquisition has been proposed by multitudinous technical workers in product design. However, most existing works are static and the product design resources have a fixed boundary. In this paper, a novel method of generating the optimal scheme for open design (OD) based on co-designer involvement and a dynamic FBSC model is proposed to tackle these problems. In OD, co-designers (consumers who have design experience and knowledge) can be involved in the process of product design to express requirements, share design knowledge and experience, etc. To support co-designers involvement in OD, a framework of the dynamic function-behaviour-structure cell (FBSC) model and its knowledge representation are presented. Based on the importance weights of design requirements, an approach for selecting SCs in the design scheme is proposed. Then a method for integrating design requirements and assembly complexity is put forward to generate the optimal design scheme. Finally, a case study is presented to demonstrate the feasibility of the proposed research.